FAKTOR FAKTOR YANG MEMPENGARUHI PRODUK DOMESTIK BRUTO NEGARA-NEGARA ASEAN PERIODE 2005-2014 - Leorista Milliardo (Jurnal Ekonomi dan Bisnis, 2017)
This study was conducted with the aim of identifying the factors affecting economic growth in ASEAN member countries during the period of 2005 - 2014, with the countries sampled in this study were six countries namely Indonesia, Singapore, Malaysia, Thailand, Philippines, Vietnam, Cambodia and Laos. The method of analysis used is the method of Data Panel Regression and Fixed Efect estimation model by using analytical tool to help process data is Eviews 7 program. While data used is panel data from eight ASEAN countries covering 10 year periods. The result of analysis shows that the acceptance of International Tourism Sector and Foreign Direct Investment has positive and significantinfluenceto the economic growth in eight ASEAN countries while the Labor Force is inconclusive. The study also found that Export of Goods and Services had a negative and significanteffect on economic growth.